Changes in Sleep Patterns Following Traumatic Brain Injury: A Controlled Study. (September 2013) - Ponsford, Jennie L.; Parcell, Diane L.; Sinclair, Kelly L.; Roper, Monique; Rajaratnam, Shantha M. W.
Background . Sleep changes are frequently reported following traumatic brain injury (TBI) and have an impact on rehabilitation and quality of life following injury. Potential causes include injury to brain regions associated with sleep regulation, as well as secondary factors, including depression, anxiety, and pain. Understanding the nature and causes of sleep changes following TBI represents a vital step in developing effective treatments. Objective . The study aimed to investigate subjective sleep changes in a community-based sample of individuals with TBI in comparison with noninjured age- and sex-matched controls and to explore the impact of secondary factors (pain, anxiety, depression, employment) on these self-reported sleep changes. Methods : A total of 153 participants with mild to severe TBI and 128 noninjured controls completed self-report measures relating to their sleep quality, daytime sleepiness, mood, fatigue, and pain and completed a sleep diary each day for 7 days. Results . Compared with the noninjured controls, participants with TBI reported significantly poorer sleep quality and higher levels of daytime sleepiness; sleep diaries revealed longer sleep onset latency, poorer sleep efficiency, longer sleep duration, and more frequent daytime napping in the TBI group, as well as earlier bedtimes and greater total sleep duration. Anxiety, depression, and pain were associated with poorer sleep quality. Greater injury severity was also associated with a need for longer sleep time. Conclusion . These findings highlight the importance of assessing and addressing pain, anxiety, and depression as part of the process of treating TBI-related sleep disturbances.